Revisiting the hybridization processes in the Triatoma brasiliensis complex (Hemiptera, Triatominae): Interspecific genomic compatibility point to a possible recent diversification of the species grouped in this monophyletic complex - Pinotti, Heloisa [UNESP]; de Oliveira, Jader [UNESP]; Ravazi, Amanda [UNESP]; Madeira, Fernanda Fernandez [UNESP]; dos Reis, Yago Visinho [UNESP]; de Oliveira, Ana Beatriz Bortolozo [UNESP]; de Azeredo-Oliveira, Maria Tercília Vilela [UNESP]; da Rosa, João Aristeu [UNESP]; Alevi, Kaio Cesar Chaboli [UNESP] (Public Library of Science (PLoS), 2021)
Triatomines are hematophagous insects of great epidemiological importance, since they are vectors of the protozoan Trypanosoma cruzi, the etiological agent of Chagas disease. Triatoma brasiliensis complex is a monophyletic group formed by two subspecies and six species: T. b. brasiliensis, T. b. macromelasoma, T. bahiensis, T. juazeirensis, T. lenti, T. melanica, T. petrocchiae and T. sherlocki. The specific status of several species grouped in the T. brasiliensis complex was confirmed from experimental crossing and analysis of reproductive barriers. Thus, we perform interspecific experimental crosses between T. lenti and other species and subspecies of the T. brasiliensis complex and perform morphological analysis of the gonads and cytogenetic analysis in the homeologous chromosomes of the hybrids of first generation (F1). Besides that, we rescue all the literature data associated with the study of reproductive barriers in this monophyletic complex of species and subspecies. For all crosses performed between T. b. brasiliensis, T. b. macromelasoma, T. juazeirensis and T. melanica with T. lenti, interspecific copulas occurred (showing absence of mechanical isolation), hybrids were obtained, none of the male hybrids presented the phenomenon of gonadal dysgenesis and 100% pairing between the chromosomes homeologous of the hybrids was observed. Thus, we demonstrate that there are no pre-zygotic reproductive barriers installed between T. lenti and the species and subspecies of the T. brasiliensis complex. In addition, we demonstrate that the hybrids obtained between these crosses have high genomic compatibility and the absence of gonadal dysgenesis. These results point to reproductive compatibility between T. lenti and species and subspecies of the T. brasiliensis complex (confirming its inclusion in the complex) and lead us to suggest a possible recent diversification of the taxa of this monophyletic group.